Physiological Equivalent Temperature (PET) and Wet-Bulb Globe Temperature (WBGT) index data from the Gothenburg half marathon. - Thorsson, Sofia; Rayner, David; Palm, Gunnar; Lindberg, Fredrik; Carlström, Eric; Börjesson, Mats; Nilson, Finn; Khorram-Manesh, Amir; Holmer, Björn (University of Gothenburg, 2020)
Aim: To identify the thermal index that best predicts exertional heat incidence risk during a city half-marathon.

Data: Eight years (2010-2017) of meteorological and ambulance transport data, including medical records, from Gothenburg’s half-marathon were used to analyze associations between WBGT, PET and UTCI and the rates of ambulance-required assistances (ARAs) and collapses.

For more information, see the attached document "Data description".

Meteorological data consisted of hourly averages of air temperature, wind speed, relative humidity, mean sea-level pressure, and incoming shortwave radiation.
Thermal comfort indices are wet bulb globe temperature index (WBGT), Physiological equivalent temperature index (PET), and Universal thermal comfort index (UTCI).

Åtta år (2010-2017) av data om meteorologiska förhållanden och ambulanstransporter, inklusive medicinska journaler, från Göteborgsvarvet (halvmaraton) användes för att analysera samband mellan WBGT, PET och UTCI och antal ambulansutryckningar (ARA) och kollapser.

För fler detaljer, se det bifogade dokumentet "Data description".

I den meteorologiska datan ingår lufttemperatur, vindhastighet, relativ fuktighet, genomsnittligt lufttryck vid havsnivån och kortvågsstrålning. Värdena är snittet för den aktuella timmen.
Värmeindexen som används är Wet bulb globe temperature index (WBGT), Physiological equivalent temperature index (PET), och Universal thermal comfort index (UTCI).
Fysiologiskt ekvivalent temperatur (PET) och Värmeindex (WBGT) - data från Göteborgsvarvet.
Keywords: wet bulb globe temperature index; värmeindex; physiological equivalent temperature; Fysiologiskt ekvivalent temperatur; endurance sport; uthållighetssport; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Sport and Fitness Sciences; Idrottsvetenskap och fitness